Exploring Gender and Identity in Ontario’s Early Years Curriculum Documents - DiMarco, Sara; Ruthes Coelho, Carla (Journal of the Canadian Association for Curriculum Studies, 2020)
Understanding how Ontario Ministry of Education (OME) early years’ curriculum and framework documents, such as The Kindergarten Program (OME, 2016), How Does Learning Happen? (OME, 2014) and ELECT (BSEPEL, 2007) set the expectations for fostering gender and identity formation is increasingly vital in contemporary society. Educators need to understand how the mandated documents feed their practice and influence what is understood by educators as “appropriate” gendered practices and identities. Drawing on a poststructural feminist perspective (Blaise & Taylor, 2012), the authors examine these early years’ documents for systemic or structural aspects that suggest the formation of specific gender identities. Specifically, this study explores the language and systemic gender beliefs contained in the three documents identified above. The study also examines how specific ideologies may influence gender identity formation in young children. The authors expect to find that these curriculum and framework documents do not support educators in fostering the formation of gender identities, particularly those which are outside of heteronormative expectations.